![{x}^{2} - 4x + 5 = 0 \\ {x}^{2} - 4x = - 5 \\ \\ { (\frac{b}{2} )}^{2} = ( \frac{ - 4}{2} ) = ( { - 2})^{2} = 4 \\ {x}^{2} - 4x + 4 = - 5 + 4 \\ {(x - 2)}^{2} = - 1 \\ {(x - 2)}^{2} + 1](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20-%204x%20%2B%205%20%3D%200%20%5C%5C%20%20%7Bx%7D%5E%7B2%7D%20%20-%204x%20%3D%20%20-%205%20%5C%5C%20%20%20%5C%5C%20%20%7B%20%28%5Cfrac%7Bb%7D%7B2%7D%20%29%7D%5E%7B2%7D%20%20%3D%20%28%20%5Cfrac%7B%20-%204%7D%7B2%7D%20%29%20%3D%20%28%20%7B%20-%202%7D%29%5E%7B2%7D%20%20%3D%204%20%5C%5C%20%20%7Bx%7D%5E%7B2%7D%20%20-%204x%20%2B%204%20%3D%20%20-%205%20%2B%204%20%5C%5C%20%20%7B%28x%20-%202%29%7D%5E%7B2%7D%20%20%3D%20%20-%201%20%5C%5C%20%20%7B%28x%20-%202%29%7D%5E%7B2%7D%20%20%2B%201)
The last line is in vertex form, and can see the vertex is located at (2,1).
What's the actual question? That's the same as the radius of the circle if that's what you're asking
The fourth term in the arithmetic sequence is 4. This is because you are subtracting 3 each time, and you already have your first three numbers in the pattern, so all you have to do is subtract another 3 in order to get 4.